Gender equality and social inclusion (GESI) assessment: Zambia, Nigeria and Kenya - Ganguly, Sujata; Drucza, Kristie; Njiriri, Wanja; Yossa, Rodrigue (WorldFish, 2024)
The Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa (FASA) project is an initiative funded by the Norwegian Agency for Development Cooperation (Norad). It operates in Nigeria, Zambia and Kenya, with research support from Malaysia and Sweden. Includovate spearheads the gender and social inclusion work under the guidance of the WorldFish project leader based in Malaysia. The primary goal is to lead gender and social inclusion (GESI) efforts within the FASA project, aiming to conduct comprehensive gender and social assessments and identify opportunities to advance GESI objectives set by Norad, WorldFish and other key stakeholders within the innovative feed landscape. To conduct this GESI assessment, the project used the Automated Directive Services (ADS 205) domains of the United States Agency for International Development, focusing on identifying key GESI-related issues and constraints. Emphasis was placed on understanding how proposed interventions would impact various social groups, including women, men, youths and other marginalized communities. The assessment involved a meticulous desk-based policy review of the legal frameworks governing the fisheries sector in Nigeria, Zambia and Kenya, analyzing existing laws, policies and regulations related to fisheries resource management, including aquaculture, from a gender perspective. This review was followed by primary data collection, employing a mixed research approach involving 28 key informant interviews (KIIs) and 420 survey responses across the three countries.